Bilingual Dictionaries for Communication in the Domain of Economics: Function-Based Translation Dictionaries - Nielsen, Sandro (HERMES - Journal of Language and Communication in Business, 2015)
With their focus on terms, bilingual dictionaries are important tools for translating texts on economics. The most common type is the multi-field dictionary covering several related subject fields; however, multi-field dictionaries treat one or few fields extensively thereby neglecting other fields in contrast to single-field and sub-field dictionaries. Furthermore, recent research shows that economic translation is not limited to terms so lexicographers who identify and analyse the needs of translators, usage situations and stages in translating economic texts will have a sound basis for designing their lexicographic tools. The function theory allows lexicographers to study these basics so that they can offer translation tools to the domain of economics. Dictionaries should include data about terms, their grammatical properties, and their combinatorial potential as well as language varieties such as British, American and international English to indicate syntactic options and restrictions on language use. Secondly, translators need to know the meaning of domain-specific terms to properly understand the differences in the structure of the domains in the cultures involved. Finally, pragmatic data will tell authors and translators how textual resources are conventionally used and what is textually appropriate in communication within the fi eld of economics. The focus will mainly be on translations between Danish and English.